Position of Information Technology in Service Sector of Indian Economy - Saxena, Kavita (Journal of Commerce and Trade, 2015)
Indian economy is one of the world’s largest economies. India has made substantial economic and social development during the recent past. It has been observed earlier that Indian economy is yet to overcome climatic shock. Information Technology (IT) is an important emerging sector of the Indian Economy. This paper examines the India’s IT industry and also studied the impact of IT on the Indian Economy. The IT sector has served as a fertile ground for the growth of a new entrepreneurial class with innovative corporate practices and has been instrumental in reversing the brain drain, raising India’s brand equity and attracting foreign direct investment (FDI) leading to other associated benefits. The Size of this sector has increased at a tremendous rate of 35% per year during the last 10 years. Its contribution to the national gross domestic product is expected to be around 12.4 by the year 2013-14, quite similar to that in the United States today. Special subsidies or export incentives are likely to be inefficient ways of stimulating the growth of the IT sector, or of positive spillovers for the rest of the economy. The same stricture applies, to some extent, to State government policies to encourage the IT sector.